Reforms and Employment in The Egyptian Labor Market: Evolution by Age From 1988 to 2006 - Irene Selwaness (Global Labor Organization (GLO), 2020)
This paper aims to study the evolution in the age composition of males' employment in the aftermath of the public sector downsizing in the 1990s -during the Economic Reform and Structural Adjustment Policies - and the new labor law in 2003. This answers the question of whether young (15-29) and older (50-59) male workers were the most likely to bear the brunt of the 1990s reforms and the new labor law in 2003. Employment, formality and hours-of-work are simultaneously estimated by maximum likelihood to control for the self-selection, using three repeated cross sectional samples from Egyptian Datasets conducted in 1988, 1998 and 2006. Results show that men aged (15-29) and those aged (50-59) were less likely, as compared to their peers in middle age (30-49), to be employed in 1998 than in 1988 (before the first reform). While informality has affected all age groups, the 30 to 49 years old were the category that experienced the most rapid increase in informality as compared to the other two age groups. Findings also show evidence of negative correlation between the probability of employment and the probability of having a formal job, indicating that those who have more incidence to work in formal jobs are more likely to remain unemployed or inactive.
Keywords: J08; J21; N35; C3; 330; Structural Adjustment Programs; Labor Supply; Informality; Simultaneous Equations; Middle-East; Egypt